Investigation on California Bearing Ratio (CBR) Value on Stabilised Peat Using Ceramic Waste - Hamzah, Nur Hanani; Zainorabidin, Adnan (Recent Trends in Civil Engineering and Built Environment, 2021)
The peat soil is often considered problematic for the development because of its low shear strength, high water content and high compressibility. This study will concentrate on waste ceramic as addictive to improved soil strength. Therefore, the problem of ceramic waste disposal is something that should be a serious concern. Rather than disposal in landfills, ceramic waste may be used in geotechnical engineering applications, which is to increase the shear strength of the soil. The main objective for this study was to determine the best ceramic waste ratio for the stabilization of the peat soil. The California Bearing Ratio (CBR) test were conducted on the study. California Bearing Ratio (CBR), tests were conducted on the mixtures of the peat soil with the ceramic dust. The sample had been curing for 7 days with different percentage of ceramic dust. The 4% and 8% of ceramic dust for unsoaked obtain CBR value of 12.7% and 29% respectively. Next sample also 4% and 8% of ceramic dust for soaked obtain CBR value of 8% and 25% respectively Keywords: Peat soil, California Bearing Ratio (CBR), ceramic waste